Why do nurses not escalate patient care when EWS indicates to do so? - Burns, Katie (2014)
Abstract Introduction Early warning scores are used worldwide as a tool to aid identification of acutely unwell patients by nursing staff. They do this by giving a patient a numerical score based upon physiological parameters. Literature review Early warning scores have been found useful in many settings and can bring about improvements in patient outcomes (for example mortality or admission to intensive care). Audit data shows that the rate of escalation is low. Aims To gain understanding of why nurses do not use early warning escalation systems appropriately and to investigate barriers to the use of EWS. Methods 14 nurses took part in semi-structured interviews. These nurses were of different bands and experience levels (including auxiliary nurses). Results and Discussion 3 main themes were brought out in the data: the gap between the theory and reality of the tool; the use of the tool being dependent upon the experience of the nurse and lack of belief in the specificity and sensitivity of the tool. Nurses often found that escalation was difficult due to lack of confidence, inability to reach staff to escalate to or other members of staff not believing in the tool. With increased experience, use of the tool decreased as nurses became more reliant upon their own knowledge and intuition. Regarding the sensitivity and specificity of the tool, nurses found that they often escalated patients who did not score high enough to trigger the system, and consequently found it difficult to be taken seriously. They also found that some patients with chronic diseases would trigger the system, but felt there was no need for this. Conclusions The use of the tool is important to improve patient outcomes. The knowledge of barriers to using the tool can be made useful in implementing change in practise.